2017
DOI: 10.3389/fpsyt.2016.00213
|View full text |Cite
|
Sign up to set email alerts
|

Non-Motor Aspects of Tic Disorders—New Developments

Abstract: The cardinal characteristics of tic-related disorders are stereotyped motor movements and vocalizations. However, they may be accompanied by non-motor features that appear sequentially during the course of the disorder and can sometimes be more disabling than the tics themselves. This review presents our perspectives on several non-motor aspects of Tourette syndrome based on the long experience of the Neuropsychiatric Tourette Clinic of a tertiary pediatric medical center. The effect of premonitory urges, sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…These disorders manifest with the sudden onset of obsessive–compulsive symptoms, tics, or a combination of both, and their symptoms are heightened during group A streptococcal infections ( Younger, 2023 ). Neuropsychological observations support a notion of TD that goes beyond a disorder of motor control and involves complex patterns of cognitive, emotional, and behavioral processes ( Ruhrman et al, 2017 ), likely affecting the domains of sensory perception ( Belluscio et al, 2011 ), sensory–motor integration ( Friedrich et al, 2021 ), attention ( Misirlisoy et al, 2015 ), and social cognition ( Channon et al, 2004 , 2012 ; Eddy and Cavanna, 2013a , 2015 ). Remarkably, these neuropsychological functions are closely related to salience-based information processing in the brain ( Seeley, 2019 ; Lugrin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 69%
“…These disorders manifest with the sudden onset of obsessive–compulsive symptoms, tics, or a combination of both, and their symptoms are heightened during group A streptococcal infections ( Younger, 2023 ). Neuropsychological observations support a notion of TD that goes beyond a disorder of motor control and involves complex patterns of cognitive, emotional, and behavioral processes ( Ruhrman et al, 2017 ), likely affecting the domains of sensory perception ( Belluscio et al, 2011 ), sensory–motor integration ( Friedrich et al, 2021 ), attention ( Misirlisoy et al, 2015 ), and social cognition ( Channon et al, 2004 , 2012 ; Eddy and Cavanna, 2013a , 2015 ). Remarkably, these neuropsychological functions are closely related to salience-based information processing in the brain ( Seeley, 2019 ; Lugrin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 69%
“…Además, la investigación ha demostrado que el estrés elevado de los padres y las diferencias en el procesamiento sensorial en los hijos están relacionados. Los niños prematuros tienen un mayor riesgo de alteración del procesamiento sensorial (Daily et al, 2019;Germain, 2018;Ruhrman et al, 2017).…”
Section: Integración Sensorial Y El Apegounclassified
“…Additionally, research has shown that high parental stress and differences in sensory processing in children are related. Premature infants are at a higher risk for impaired sensory processing (Daily et al, 2019;Germain, 2018;Ruhrman et al, 2017). Acosta Manjarres's (2020) research has also found that attachment and parenting patterns significantly influence the physical, social, and mental development of children, and should be evaluated by health professionals.…”
Section: Sensory Integration and Attachmentmentioning
confidence: 99%